МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ЛАНОК ПІДСИСТЕМИ АНТИПОМПАЖНОГО РЕГУЛЮВАННЯ КОМПРЕСОРНОЇ СТАНЦІЇ ПІДЗЕМНОГО СХОВИЩА ГАЗУ - Гіренко, С. Г. (Oil and Gas Power Engineering, 2008)
The mathematical models of such links are examined as konfuzor, centrifugal supercharger, bolts, losses, forks of gas pipeline, which allow to provide description of object and subsystem antipompag adjusting of the automatic control the centrifugal over aggregate of the compressor station of dug-out of gas of "Bilche-Volitsa".